2017
DOI: 10.1371/journal.pone.0175250
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol-functionalized poly (Lactic Acid-co-Glycolic Acid) and graphene oxide nanoparticles induce pro-inflammatory and apoptotic responses in Candida albicans-infected vaginal epithelial cells

Abstract: Mucous-penetrating nanoparticles consisting of poly lactic acid-co-glycolic acid (PLGA)-polyethylene glycol (PEG) could improve targeting of microbicidal drugs for sexually transmitted diseases by intravaginal inoculation. Nanoparticles can induce inflammatory responses, which may exacerbate the inflammation that occurs in the vaginal tracts of women with yeast infections. This study evaluated the effects of these drug-delivery nanoparticles on VK2(E6/E7) vaginal epithelial cell proinflammatory responses to Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
1
19
2
Order By: Relevance
“…The developed formulation exhibited a remarkable improvement (roughly five-fold) in the sustained delivery of the drug in comparison to the non-adhesive alternative formulation. The results of the research highlighted the potential of the adhesive PLA-HPG nano-formulation for intravaginal therapeutics to treat and prevent STIs [65]. Aside from STIs associated with HSV, Wagner et al [66] developed a nanoparticle-based targeted approach that comprised microbicidal drugs encapsulated in mucous-penetrating PLGA-PEG nanoparticles for intravaginal inoculation against STIs.…”
Section: Sexually Transmitted Infections and Hivmentioning
confidence: 99%
“…The developed formulation exhibited a remarkable improvement (roughly five-fold) in the sustained delivery of the drug in comparison to the non-adhesive alternative formulation. The results of the research highlighted the potential of the adhesive PLA-HPG nano-formulation for intravaginal therapeutics to treat and prevent STIs [65]. Aside from STIs associated with HSV, Wagner et al [66] developed a nanoparticle-based targeted approach that comprised microbicidal drugs encapsulated in mucous-penetrating PLGA-PEG nanoparticles for intravaginal inoculation against STIs.…”
Section: Sexually Transmitted Infections and Hivmentioning
confidence: 99%
“…Vulvovaginal candidiasis is an opportunistic fungal infection predominantly caused by overgrowth of Candida albicans that colonizes the vagina. The infection induces a strong inflammatory response in localized vaginal and vulvar epithelial tissues [ 1 ]. It remains the most prevalent organism in both mucosal and systemic yeast infections.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that vaginal epithelial cells (VEC) in vitro contribute to inflammatory recruitment by secreting inflammatory cytokines after recognizing C . albicans through Nod-like receptors and a pyroptosis mechanism [ 1 ]. Though the innate immune response is required for clearance of C .…”
Section: Introductionmentioning
confidence: 99%
“…Our group has focused on the production of nanoparticles composed of a polyethylene glycol diacrylate (PEGDA)–n‐vinyl pyrrolidone (NVP) crosslinked hydrogel matrix encapsulated with phosphate salts and synthesized using an inverse miniemulsion polymerization process . Polyethylene glycol (PEG)‐coated nanoparticles, or PEGylated nanoparticles have demonstrated significant promise in drug delivery research as their surface does not promote non‐specific tissue binding while allowing for deeper penetration and longer circulation times especially in mucosal tissues . However, it must be noted that in these prior studies the nanoparticles investigated were composed of different material structures (linear polymers or crystalline materials ) and subsequently surface‐coated with PEG.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG)‐coated nanoparticles, or PEGylated nanoparticles have demonstrated significant promise in drug delivery research as their surface does not promote non‐specific tissue binding while allowing for deeper penetration and longer circulation times especially in mucosal tissues . However, it must be noted that in these prior studies the nanoparticles investigated were composed of different material structures (linear polymers or crystalline materials ) and subsequently surface‐coated with PEG. The development of crosslinked hydrogel PEG nanoparticles for drug delivery applications is rare.…”
Section: Introductionmentioning
confidence: 99%